Two-way bioinvasion: tracking the neritic non-native cyclopoid copepods Dioithona oculata and Oithona davisae (Oithonidae) in the Eastern Mediterranean Sea - VELASQUEZ, XIMENA; MOROV, ARSENIY R.; TERBIYIK KURT, TUBA; MERON, DALIT; GUY-HAIM, TAMAR (Mediterranean Marine Science, 2021)
Accelerated anthropogenic changes in the Eastern Mediterranean Sea (EMS) have facilitated the introduction, spread and establishment of invasive copepod species in this region. Here, we report the introduction of two non-native cyclopoid copepods Dioithona oculata and Oithona davisae for the first time in the Israeli coastal waters and describe their temporal variability. The species were identified by morphological characteristics, DNA barcoding and phylogenetic inference. Molecular identification and phylogenetic analysis supported the taxonomical identification, nevertheless, showed cryptic speciation within D. oculata, separating the Western Pacific and EMS clades. In the Israeli coastal waters, D. oculata presented a temporally restricted occurrence, appearing from September 2019 to December 2019 (30.0±0.7 – 21.0±1.1 °C) and October 2020 (28.0±0.7 °C). The highest abundances of D. oculata occurred in the autumn (October 2019 and 2020), when the water temperature reached 28.0 °C (7 and 10 ind. m-3, respectively). The lowest abundance occurred in December 2019 (0.35 ind. m-3), when the water temperature decreased to 21.0 °C, indicating that the thermal affinity of D. oculata for warm-temperate conditions, for reproduction and the maintenance of viable populations, has persisted in the introduced range. In contrast, O. davisae appeared almost all year around (17.0±0.5 – 28.0±0.7 °C). This species demonstrated peaks in abundance both in October 2019 and October 2020, when the water temperature reached 28.0 °C (406 and 92 ind. m-3), as well as when the temperature decreased to 17.0 °C (31 ind. m-3, February 2020), confirming its wide eurythermal tolerance. Based on our findings and previous observations, we suggest that D. oculata may have invaded the EMS through the Suez Canal and is now at the onset of its spread in the Mediterranean Sea, whereas O. davisae has been introduced via shipping, likely from the Northeast Atlantic, widely spreading and successfully establishing viable populations across the entire Mediterranean Sea, until the coastal Levantine Sea.